Is the Energy-led Growth Hypothesis Valid? New Evidence From a Sample of 85 Countries - Apergis, Nicholas; Tang, Chor (Elsevier, 2013)
The energy-growth literature contains a large number of discussions on the causal relationship between energy consumption and economic growth. The central debate focuses on whether energy consumption contributes or not to economic growth since it has direct implications for the formulation of strategic policies. Nevertheless, current studies cannot provide a conclusive suggestion due to mixed causality results. This inconclusive evidence is potentially attributed to model specifications and the stage of economic development of the countries under investigation. Hence, this study attempts to empirically re-investigate the validity of the energy-led growth hypothesis using a different model specification and different stages of economic development for 85 selected countries around the globe. Overall, although the causality results are mixed among countries, we do find a systematic pattern. In particular, Granger causality models with three and four variables are more likely to support the hypothesis compared to their counterparts that contain only two variables. In addition, both developed and developing countries are more likely to support the energy-led growth hypothesis compared to the less developed or low income countries. Therefore, causality results are very sensitive to the choice of the model specification along with the stages of economic development. Finally, energy conservation policies should only focus on low income countries as these policies may not retard the process of economic growth.